Influence of the housing system on carcass composition and meat quality of laying hens after the laying period - Marcin Wegner; Dariusz Kokoszyński; Joanna Żochowska-Kujawska; Marek Kotowicz; Joanna Frischke-Krajewska (Poultry Science)
The purpose of the present study was to compare the effects of two systems of keeping Lohmann Brown laying hens in terms of carcass composition and meat quality assessment (chemical composition, physicochemical properties, texture, rheological properties, microstructure). The experimental material consisted of 30 carcasses (15 litter system - SS, 15 aviary system - SW) of Lohmann Brown laying hens after laying at 85 weeks of age. After slaughtering, the weight of the eviscerated carcass and the proportion of carcass elements, the weight of selected internal organs, acidity (pH24), and electroconductivity (EC24), color (L*, a*, b*), and the basic chemical composition of pectoral muscles and leg muscles were determined. The texture, rheological properties, and microstructure of the pectoralis major muscle were analyzed. The housing system affected the percentage of abdominal fat (SW - 2.10% vs. SS - 0.81%) and skin with subcutaneous fat (SW - 11.84% vs. SS - 10.89%). There were also differences in the weight of the giblets (proventriculus, gizzard, liver, heart). The housing system also affected the fiber cross-sectional area (SW - 660.01 µm2 vs. SS - 674.53 µm2). The present study provided information on the differences in some carcass traits and the quality of meat of Lohmann Brown hens depending on the housing system.